Use of Steam Technologies in Primary Class Lessons (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
In the article, the use of STEAM technologies in educational activities in primary education, by developing didactic methods of effectively organizing, mastering, and applying knowledge skills of students achieve the formation of work skills. Elucidation of methodical methods of effective use of STEAM technologies in primary education, evaluation of students' creative abilities based on didactic methods in training classes, and achievement of students' initial understanding of specific subjects.